THE DEVELOPMENT OF THE THEORY AND PRACTICE OF PROJECT MANAGEMENT: THE ROLE OF THE SCIENTIFIC SCHOOL OF THE STATE UNIVERSITY OF MANAGEMENT (PART 2) - G. Ya. Soroko; I. Z. Kogotkova (Вестник университета, 2019)
This article is a continuation of the publication of the results of the study of the evolution of project management as a special type of management activity. The main events from the history of formation and development of the theory and practice of project management as a result of scientific research of scientists of the State University of Management have been highlighed. The history of development and the current state of the theory of project management in the State University of Management are associated with the actual needs of management practice both during the twentieth century and now, because the improvement of the mechanism of project management is one of the strategies for the development of the country’s economy.